Emotional Intelligence on Learning English as English Foreign Language - Ifan Alfaeni; Abdul Muin Bahaf; Tatu Siti Rohbiah (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2022)
The focus of this study was on students' emotional intelligence when learning English as a foreign language in the eleventh grade of MA Al-Khairiyah Pipitan's social sciences major. The goal of this study was to find out why students felt frightened, nervous, and uninterested in studying English, as well as how to overcome their emotional intelligence. The participants in this study were ten men and women in their eleventh year of MA Al-Khairiyah Pipitan specializing in social sciences (5 males and 5 females). The researcher has only taken one class and is a social science major. This study was designed as a descriptive qualitative study, with data gathered through observation and interviews. The results revealed that students' emotional intelligence was divided into four categories: apprehensive (42.75%), nervous (26%), embarrassed (19.75%), and not confident (5.25%). Students have their own strategies for dealing with their emotions. As a result, many students had anxiety when learning English and the only method to overcome emotional intelligence was to study hard about English